Analisis Titik Lokasi Base Transceiver Station Berdasarkan Faktor Daerah Fresnel - Agam Febriansyah; Fatoni (STMIK Budi Darma, 2023)
Telecommunications and information technology have become an important part of everyday life, but the problem of poor networks is still a challenge in many areas, including the province of South Sumatra, Indonesia. PT Julian Adiputra Utama (PT JAU), as a telecommunications and information technology company, is trying to overcome this problem by building a Base Transceiver Station (BTS) tower to improve connectivity and information accessibility for the local community. The aim of this research is to analyze the determination of the most effective BTS tower installation locations based on the Fresnel area factor. The Fresnel zone around the signal transmission path between the BTS and the receiver is a critical area that can cause interference and reduce signal quality. Considering the Fresnel zone, this research looks for suitable location points for installing BTS towers to improve signal quality and efficiency of telecommunications services. The search method includes selecting 10 candidate locations as possible locations for installing BTS towers, followed by traffic design and driving tests. Fresnel area data is calculated using the formula rf = 17.32 taking into account the curvature of the earth and the height of the antenna. The calculation results show that candidate R was chosen as the most effective detection point because it has a larger Fresnel area than the other candidates. This research has important implications for planning and developing telecommunications infrastructure, especially for improving connectivity in remote areas. Accessibility of information and telecommunications services to the public in South Sumatra Province is expected to increase if effective BTS placement points are determined based on Fresnel area analysis.